Discordance between lifestyle-related health beliefs and behaviours of Saudi women in Dammam. (August 2017) - Al-Bannay, Hana R; Jarus, Tal; Jongbloed, Lyn; Dean, Elizabeth
Objective: Women living in the Kingdom of Saudi Arabia including in the Eastern Province have a high prevalence of lifestyle-related conditions for which targeted health education strategies are needed. This study's objective was to explore their self-reported health status and the congruence of their lifestyle-related health beliefs and practices to inform health education programme development. Methods: A cross section of community-living Saudi women ( N  = 407) living in Dammam (the capital of the Eastern Province) was sampled from regional health centres. Participants completed an interview survey questionnaire about their health status and their lifestyle-related health beliefs and practices. Results: In all, 44% of participants reported having an average but not excellent health. This finding was at odds with their unequivocal, evidence-supported beliefs about the positive relationship between exercise, good nutrition, not smoking and manageable stress, with health (⩾97%). Despite these strong beliefs, participants reported suboptimal levels of exercise, nutritional choices, stress and sleep quality and quantity for maximal health and wellbeing. Conclusion: Studies are warranted to explore and explain marked discrepancy between the positive health beliefs and lifestyle-related health practices of Saudi women living in Dammam, and to design effective health promotion education programmes to address this gap. Improving Saudi women's health by narrowing the lifestyle-related health belief–practice gap may also maximise the health of families, given women's pivotal role in managing the family, as well as individual health.